Association of Craniofacial Patterns with the Curve of Spee and the Time Required for Orthodontic Levelling - Annina Krüsi; Konstantinos Dritsas; Eleni Kalimeri; Dimitrios Kloukos; Nikolaos Gkantidis (MDPI AG, 2022)
The curve of Spee (CoS) is an important parameter for an individualized treatment plan. The available information regarding a potential association of the depth of the curve of Spee with various skeletal craniofacial characteristics is conflicting and it is also unknown whether certain craniofacial parameters affect the duration of the levelling phase of orthodontic treatment. A prospective sample of 32 patients with mild to moderate crowding that underwent orthodontic treatment with full fixed appliances was used to study these topics. The craniofacial characteristics were captured on pre-treatment lateral cephalometric radiographs and measurements of the CoS were performed on the initial 3D digital dental models using the Viewbox 4 software. Non-parametric statistics and Spearman's correlations were applied. Weak negative correlations were detected between the CoS depth and the SNA and SNB angles. There was no other association between the CoS and craniofacial parameters, including various anteroposterior measurements. Furthermore, there was no significant association of any craniofacial parameter with the duration of the levelling. Contrary to certain clinical beliefs, it can be argued that the craniofacial characteristics are not associated with the CoS and the time required for its levelling in subjects with moderate pre-treatment CoS depth.